A Floral Diet Increases the Longevity of the Coccinellid Adalia bipunctata but Does Not Allow Molting or Reproduction - He, Xueqing; Sigsgaard, Lene (Frontiers in Ecology and Evolution, 2019)
Adalia bipunctata L. (Coleoptera: Coccinellidae) is a generalist aphidophagous coccinellid and an important natural enemy in many agroecosystems including orchards. Coccinellid species have been observed to consume non-prey food like nectar and pollen, but the value of these foods for A. bipunctata is poorly known. The objective of this study was to determine the effect of different prey and non-prey diets on A. bipunctata larval development and adult longevity and fecundity. Larval development was studied on three prey diets: The aphids Dysaphis plantaginea and Myzus persicae and Lepidopteran eggs of Ephestia kuehniella; five flower diets: Matricaria chamomilla, Daucus carota, Fagopyrum esculentum, Anethum graveolens and Sinapis alba; four pollen diets from three plant species: Typha angustifolia, Malus pumila (two varieties) and A. graveolens; and 1 M solutions of three sugars: glucose, fructose and sucrose. Adult longevity and fecundity were tested on one prey diet (E. kuhniella eggs), three flower diets (F. esculentum, A. graveolens and S. alba); the same four pollen diets and three sugar diets with larvae; and finally a mixed diet of sucrose and A. graveolens pollen. A water-only (starvation) control was used for both larval development and adult longevity and fecundity. Adult lipid content was assessed as a measure of how non-prey food affects the ladybeetles’ nutritional status. Larvae did not develop beyond the first instar on any of the non-prey diets, but they lived more than twice as long as on F. esculentum and sugar diets than on water. Sugar and flower diets improved A. bipunctata adult longevity (71-92 d and 10-66d, respectively) over a pure pollen diet (6-7d). Fecundity was nil on all non-prey diets, and within a normal range on E. kuhniella eggs. The results suggest that pure floral diets do not support A. bipunctata molting or reproduction, but flowering plants can prolong A. bipunctata larval survival and adults longevity considerably when prey are absent. Adults on sugar diets had high lipid content, indicating that sugar feeding can improve overwintering survival. The findings could be used in agroecosystem design, such as the composition of flower strips for optimal functional diversity.